Solid Gel Electrolytes with Highly Concentrated Liquid Electrolyte in Polymer Networks and Their Physical and Electrochemical Properties and Application to Sodium Secondary Batteries. Issue 4 (1st April 2022) - Yokomaku, Yuji; Hiraoka, Koji; Inaba, Kohei; Seki, Shiro
Abstract : Gel polymer electrolytes consisting of sulfolane (SL)-NaN(SO2 CF3 )2 liquid electrolyte and a polyether-based host polymer were prepared, and their physicochemical and electrochemical properties were investigated. The prepared gel electrolytes generally exhibited high thermal stability regardless of the NaN(SO2 CF3 )2 concentrations. The glass transition temperature decreased with the NaN(SO2 CF3 )2 concentration owing to the strong interaction between SL and Na + . The ionic conductivities of all gel polymer electrolytes were higher than 10 −4 S cm −1 at 303.15 K as a result of the plasticizer effect of SL. Although a relatively large interfacial resistance of the electrolyte/Na metal electrode was observed owing to the high reactivity of the SL-NaN(SO2 CF3 )2 electrolyte, the fabricated [Na metal negative electrode∣gel polymer electrolyte∣sulfur-modified polyacrylonitrile positive electrode] cell, i.e., the Na-S battery, achieved reversible charge-discharge operation at 333 K and demonstrated its potential to serve as an electric power storage system capable of low-temperature operation.